Fatores que influenciam a implementação de serviços clínicos farmacêuticos em hospitais : identificação e análise pelo framework Apoteca - Onozato, Thelma (2018)
Introduction. The implementation of Clinical Pharmacy Services (CPS) is a strategic action to optimize the pharmacotherapy of hospitalized patients. Although many studies have shown beneficial results for CPS, they are not uniformly established in hospitals worldwide, including in Brazil. To know the factors that influence CPS deployment and to identify where they act is the first step toward successful adoption of these services in hospitals. Aim. To identify the factors that affect the CPS implementation in the hospital setting and to analyze them using the Apoteca domains. Methods. The study was carried out in five stages. (1) Framework development to analyze factors that influence the implementation of SCF. For this, systematic observations were made during SCF implementation experiences conducted by the researchers and analysis of conceptual models based on observations of reality were performed. (2) Systematic review of the literature to identify factors that influence the implementation of CPS in the hospital setting. Six databases were searched until January 2018. The search strategy was developed using terms related to: “clinical pharmacy”, “influencing factors”, “implementation” and “hospital”. Two reviewers selected original articles, extracted data and assessed the quality of the studies. After the framework synthesis and categorization of the factors in groups of interest and Attitudinal, Political, Technical and Administrative domains (Apoteca), a diagrammatic approach was used to present the results. (3) Focus group with pharmacists and interviews with hospital managers were carried out to know the perceptions about the factors that could influence the implementation of CPS in the hospital studied. (4) Structured implementation intervention with attitudinal, political, technical and administrative approaches. (5) Interviews were carried out with the pharmacists who performed the CPS and managers, to know the participants' perceptions of the factors that actually influenced the CPS implementation in the hospital. After collecting the information, the audio records were transcribed and analyzed using framework analysis and the Apoteca domains, in order to compare the perceptions before and after the structured SCF implementation. Results. Four domains were proposed to analyze the factors influencing the SCF implementation: Attitudinal, Political, Technical and Administrative – the Apoteca framework. Fifty-three factors were identified in the 21 studies included in the review. The most cited influencing factors were uniformly distributed in the four Apoteca domains, but in terms of interest groups, the “pharmacist” had the highest concentration of factors. “Clinical skills and knowledge” was the most cited factor, followed by “Time to implement CPS”. In the intervention study, pharmacists reported 19 obstacles in total, while managers perceived 16 different barriers. About half of the barriers cited were considered to have been overcome or not-met in the second interview. Managers and pharmacists mentioned fewer facilitators when compared to barriers (eleven and ten, respectively), and the latter were only able to perceive them after the intervention. Regarding the Apoteca classification, most of the barriers were administrative and the majority of the facilitators were political. Conclusion. The results showed the multifactorial nature of the CPS deployment process and that pharmacists and managers anticipated more barriers and less facilitators when compared to the factors actually experienced. Those findings suggest that a structure implementation, considering the four Apoteca domains, can help in planning strategies to enable the successful implementation of CPS in a hospital setting.